Diagnostic Dilemma between Atypical Meningioma and Glioblastoma-Our Observation - Akhlaque Hossain Khan; Mehedi Hasan Munna; Muhammad Saiful Islam; Sumaiya Rahman; Tofayel Ahmed; Jalal Ahmed Ripon; Rahatul Islam; Ariful Islam; Abdullah Al Mamun; Tandin Wangyel Dorji; Anik Biswas; Md Abu Obaida, Abu Saleh; et al. (Bangladesh Journal of Neurosurgery, 2024)
Both meningioma and glioblastoma are very common intra-cranial neoplasm. Typically both have distinguishing clinical and radiological features which aid in diagnosis and thus pre-operative preparation, planning, counseling the patient etc. But dilemma may often arise in case of non-grade-I meningioma making confusion in favor of higher grade astrocytoma (glioblastoma). In that case total per-operative picture, surgical approach, post- operative managements, and disease prognosis will be altered. We faced such kind of confusion in a case so reported here. Bang. J Neurosurgery 2023; 13(1): 44-47